2014
DOI: 10.1590/s0103-90162014000300002
|View full text |Cite
|
Sign up to set email alerts
|

Plant densities and modulation of symbiotic nitrogen fixation in soybean

Abstract: Soybean nitrogen (N) demands can be supplied to a large extent via biological nitrogen fixation, but the mechanisms of source/sink regulating photosynthesis/nitrogen fixation in high yielding cultivars and current crop management arrangements need to be investigated.We investigated the modulation of symbiotic nitrogen fixation in soybean [Glycine max (L.) Merrill] at different plant densities. A field trial was performed in southern Brazil with six treatments, including non-inoculated controls without and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
2
28
1
7
Order By: Relevance
“…According to TOURINO et al (2002), there is a direct relationship between plant density and lodging, it is expected that an increase in the population will increase lodging. In literature, other studies showed low response of soybean grain yield to plant density variations (DE LUCA & HUNGRIA, 2014;BALBINOT JUNIOR et al, 2015). These results may be related to the high phenotypic plasticity of soybean.…”
Section: Resultsmentioning
confidence: 82%
“…According to TOURINO et al (2002), there is a direct relationship between plant density and lodging, it is expected that an increase in the population will increase lodging. In literature, other studies showed low response of soybean grain yield to plant density variations (DE LUCA & HUNGRIA, 2014;BALBINOT JUNIOR et al, 2015). These results may be related to the high phenotypic plasticity of soybean.…”
Section: Resultsmentioning
confidence: 82%
“…Isso demonstra que as variações de rendimento de grãos em razão do manejo adotado são decorrentes, fundamentalmente, do número de legumes por planta e, consequentemente, por área, sendo as demais características avaliadas pouco afetadas pelo arranjo espacial das plantas. No primeiro experimento, não houve efeito da densidade de plantas sobre o rendimento de grãos (Tabela 3), demonstrando a grande plasticidade fenotípica da soja (RAMBO et al, 2004;HEIFFIG et al, 2006;CHERNEY, 2011;BOARD;KAHLON, 2013;LUCA;HUNGRIA, 2014). Todavia, no segundo experimento, a menor densidade de plantas conferiu maior rendimento de grãos (Tabela 4), demonstrando que, em semeadura mais tardia, o uso de altas densidades de plantas acentua demasiadamente a competição intraespecífica, tornando a redução da produção por planta mais expressiva do que o aumento no número de plantas por área.…”
Section: Resultsunclassified
“…, porcentagem dos legumes provenientes dos ramos e porcentagem da massa de grãos provenientes dos ramos na menor densidade de plantas avaliada (Tabelas 3 e 4). Isso ocorreu porque, nessa situação, a disponibilidade de água, luz e nutrientes para cada indivíduo é maior, conferindo maior produção por planta e melhores condições para a ramificação (RAMBO et al, 2003;BOARD;KAHLON, 2013;LUCA;HUNGRIA, 2014).…”
Section: Resultsunclassified
“…Isso demonstra que as variações de rendimento de grãos em razão do manejo adotado são decorrentes, fundamentalmente, do número de legumes por planta e, consequentemente, por área, sendo as demais características avaliadas pouco afetadas pelo arranjo espacial das plantas. No primeiro experimento, não houve efeito da densidade de plantas sobre o rendimento de grãos (Tabela 3), demonstrando a grande plasticidade fenotípica da soja (RAMBO et al, 2004;HEIFFIG et al, 2006;CHERNEY, 2011;BOARD;KAHLON, 2013;LUCA;HUNGRIA, 2014). Todavia, no segundo experimento, a menor densidade de plantas conferiu maior rendimento de grãos (Tabela 4), demonstrando que, em semeadura mais tardia, o uso de altas densidades de plantas acentua demasiadamente a competição intraespecífica, tornando a redução da produção por planta mais expressiva do que o aumento no número de plantas por área.…”
Section: Resultsunclassified
“…Foi constatado maior número de nós no caule, número de ramos planta -1 , número de legumes no caule e nos ramos planta -1 , porcentagem dos legumes provenientes dos ramos e porcentagem da massa de grãos provenientes dos ramos na menor densidade de plantas avaliada (Tabelas 3 e 4). Isso ocorreu porque, nessa situação, a disponibilidade de água, luz e nutrientes para cada indivíduo é maior, conferindo maior produção por planta e melhores condições para a ramificação (RAMBO et al, 2003;BOARD;KAHLON, 2013;LUCA;HUNGRIA, 2014).…”
Section: Resultsunclassified